IMAGINARY EXPRESSION OF FORM AND CONTENT IN ISAJAN SULTAN'S WORKS - Maksutbaeva Nigora Rashid qizi (American Journals, 2024)
In this story, thoughts and comments are made about the artistic analysis of Isajon Sultan's works. In the early works of the artist, there are thoughts about the raised spirit, the comparison of the created national values with the works of the years of independence, and the definition given to the works of Isajon Sultan today. The article also contains views on the artistic changes in the artist's life, the fact that the artistic thinking and the style of the artistic image before the years of independence have changed after independence, and a new mentality and description is presented. The views of famous scientists and artists such as Abdugafur Rasulov, Mashhura Sheraliyeva, etc., were also discussed regarding the work of Isajon Sultan.
Keywords: Literary description, types of education, understanding of style and form, vocabulary skills.